Health Belief Model’s Application in Blood Donation Policies - Theodoratou, Maria; Papandreou, Drosoula; Dafogianni, Chrysoula; Papathanassiou, Ioanna V.; Flora, Katerina; Yotsidi, Vasiliki (International Conference on Business and Economics - Hellenic Open University, 2025)
Blood donation is a critical public health necessity, yet many countries, including Greece, face persistent challenges in maintaining a sufficient and sustainable blood supply. The Health Belief Model (HBM) offers a robust framework for understanding the motivations and barriers influencing blood donation behaviors. This study aims to investigate the factors that affect blood donation at a hospital in a rural region of Greece (i.e., Agrinio General Hospital), focusing on demographic variables and the six HBM constructs: perceived severity, perceived susceptibility, perceived benefits, perceived barriers, cues to action, and self-efficacy. A cross-sectional survey was conducted with 165 voluntary blood donors between February and April 2023. Data were collected using a structured questionnaire based on the HBM framework and analyzed using descriptive and inferential statistics. The majority of participants were male (55.76%), aged 31–50 years (30.30%), and employed full-time (90.32%). Donors demonstrated high perceived severity of blood shortages (66.7%) and significant altruistic motivation (87.2%). Key barriers included fear of needles (71.5%) and practical difficulties such as inconvenient donation hours (72.1%). Cues to action, including SMS reminders (57.6%) and proximity of donation events (48.5%), were critical facilitators. Self-efficacy was high, with 74% expressing confidence in their ability to donate regularly. In conclusion, demographic factors and HBM constructs were found to significantly influence blood donation behavior. Addressing psychological barriers, enhancing accessibility, and leveraging cues to action can improve donor recruitment and retention. These findings provide actionable insights for designing targeted strategies to achieve sustainable blood supply systems in Greece and similar contexts. JEL Classifications: I12, I18 Keywords: Blood donation, psychological attitudes, blood transfusion, Greece